MANAJEMEN SUMBER DAYA MANUSIA PADA LEMBAGA PENDIDIKAN ISLAM DI MTS PERSIS WARUDOYONG - Rayhan Fadhlan Andani; Sofwan Sofwan; Adi Rosadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research examines human resource management (HRM) in Islamic educational institutions, focusing on the problem of the lack of effective HRM that affects the quality of education and institutional performance. It aims to identify HRM practices that can improve the performance of Islamic education institutions. Qualitative research methods were used, involving in-depth interviews, observation, and document analysis at several Islamic education institutions in MTs Persis Warudoyong. The results showed that training and professional development, performance appraisal system, motivation and incentives, and effective leadership are key factors in good HR management. In conclusion, effective HR management is very important to improve the performance and quality of education in Islamic educational institutions, so that proven effective HR management strategies are needed to achieve higher and sustainable educational goals